Racial differences in cigarette brand recognition and impact on youth smoking - Dauphinee Amanda L (BMC Public Health, 2013)
Abstract Background African Americans are disproportionately exposed to cigarette advertisements, particularly for menthol brands. Tobacco industry documents outline strategic efforts to promote menthol cigarettes to African Americans at the point of sale, and studies have observed more outdoor and retail menthol advertisements in neighborhoods with more African-American residents. Little research has been conducted to examine the effect of this target marketing on adolescents’ recognition of cigarette brand advertising and on smoking uptake. To our knowledge, this is the first study to examine racial differences in brand recognition and to assess the prospective relationship between brand recognition and smoking uptake. Methods School-based surveys assessing tobacco use and environmental and social influences to smoke were administered to 6th through 9th graders (ages 11 to 15) in an urban and racially diverse California school district. The primary outcome for the cross-sectional analysis (n = 2,589) was brand recognition, measured by students’ identification of masked tobacco advertisements from the point of sale. The primary outcome for the longitudinal analysis (n = 1,179) was progression from never to ever smoking within 12 months. Results At baseline, 52% of students recognized the Camel brand, 36% Marlboro, and 32% Newport. African-American students were three times more likely than others to recognize Newport (OR = 3.03, CI = 2.45, 3.74, p < 0.01) and less likely than others to recognize Marlboro (OR = 0.60, CI = 0.48, 0.73, p < 0.01). At follow-up, 17% of never smokers reported trying smoking. In this racially diverse sample, brand recognition of Camel and Marlboro did not predict smoking initiation. Regardless of race, students who recognized the Newport brand at baseline were more likely to initiate smoking at follow-up (OR = 1.49, CI = 1.04, 2.15, p < 0.05) after adjusting for shopping frequency and other risk factors. Conclusions The study findings illustrate that African-American youth are better able to recognize Newport cigarette advertisements, even after adjustment for exposure to smoking by parents and peers. In addition, recognition of Newport cigarette advertising predicted smoking initiation, regardless of race. This longitudinal study contributes to a growing body of evidence that supports a ban on menthol flavored cigarettes in the US as well as stronger regulation of tobacco advertising at the point of sale.